2013
DOI: 10.1007/s00421-012-2582-7
|View full text |Cite
|
Sign up to set email alerts
|

Circulating pro-inflammatory cytokines are elevated and peak power output correlates with 25-hydroxyvitamin D in vitamin D insufficient adults

Abstract: The purpose of this study was to identify circulating cytokines, skeletal muscle strength, and peak power output in young adults with contrasting serum 25-hydroxyvitamin D (25(OH)D) concentrations. Serum 25(OH)D, inflammatory cytokines, muscle strength, and peak power output were, therefore, measured in young adults (25-42 years). Data were collected during the winter to avoid the seasonal influence on serum 25(OH)D. After serum 25(OH)D concentration measurements, subjects were separated into one of two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 77 publications
1
44
1
Order By: Relevance
“…In healthy adults, muscle strength was not significantly different despite contrasting serum 25(OH)D with [10] or without [5] supplemental vitamin D. However, a serum 25(OH)D concentration P 30 ng/mL improved strength recovery following anterior cruciate ligament surgery in otherwise healthy adults [46], and supplemental vitamin D (4000 IU/d of cholecalciferol) increased serum 25(OH)D (%47 ng/mL) and enhanced strength recovery following exercise-induced muscle damage in young adults [31]. Based on the evidence, muscle performance at rest or in the absence of injury may not be impaired with a low serum 25(OH)D concentration (e.g., >6 but <29 ng/mL), but maintaining or achieving a sufficient serum 25(OH)D concentration (i.e., P30 ng/mL) could be beneficial on the physical rehabilitation from a muscular or ligamentous injury in physically active and otherwise healthy adults.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In healthy adults, muscle strength was not significantly different despite contrasting serum 25(OH)D with [10] or without [5] supplemental vitamin D. However, a serum 25(OH)D concentration P 30 ng/mL improved strength recovery following anterior cruciate ligament surgery in otherwise healthy adults [46], and supplemental vitamin D (4000 IU/d of cholecalciferol) increased serum 25(OH)D (%47 ng/mL) and enhanced strength recovery following exercise-induced muscle damage in young adults [31]. Based on the evidence, muscle performance at rest or in the absence of injury may not be impaired with a low serum 25(OH)D concentration (e.g., >6 but <29 ng/mL), but maintaining or achieving a sufficient serum 25(OH)D concentration (i.e., P30 ng/mL) could be beneficial on the physical rehabilitation from a muscular or ligamentous injury in physically active and otherwise healthy adults.…”
Section: Discussionmentioning
confidence: 81%
“…In a previous study, we found a pro-inflammatory cytokine increase in subjects with an insufficient serum 25(OH)D concentration [5]. Therefore, we examined the influence of supplemental vitamin D status at Bsl on serum cytokine changes after supplemental vitamin D. Subjects categorized as vitamin D deficient (serum 25(OH)D < 20 ng/mL) and insufficient (serum 25(OH)D 20-29 ng/mL) before supplementation were pooled into one group due to few subjects in each group respectively (see Table 1).…”
Section: Cytokinesmentioning
confidence: 96%
See 1 more Smart Citation
“…Vitamin D status has been associated with reduced circulatory inflammatory markers and concomitant impairments in peak power in healthy adults (4). Serum 25OHD also has been implicated in skeletal muscle recovery after exercise and injury (3,16,41).…”
Section: Potential Effects Of Vitamin D On Biological Pathways In Musclementioning
confidence: 99%
“…Within the general population it has been reported that circulating proinflammatory cytokine concentrations, such as TNF- α , IFN- γ , IL-1 β , and IL-2, were significantly higher in vitamin D insufficient adults compared with those who were vitamin D sufficient [9]. However, to our knowledge, there has been no study to compare the difference in circulating cytokine levels between vitamin D insufficient and sufficient athletes.…”
Section: Introductionmentioning
confidence: 99%